1999
DOI: 10.1164/ajrccm.159.4.9805017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Idiopathic Pulmonary Fibrosis with a New Antifibrotic Agent, Pirfenidone

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive clinical syndrome of unknown etiology and fatal outcome. Currently available therapies are ineffective and associated with significant adverse effects. Pirfenidone, a new, investigational antifibrotic agent, was evaluated for its tolerability and usefulness in terminally ill patients with advanced IPF. Consecutive patients with IPF and deterioration despite conventional therapy or who were unable to tolerate or unwilling to try conventional therapy were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
245
1
18

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(277 citation statements)
references
References 23 publications
13
245
1
18
Order By: Relevance
“…It was not our aim to examine whether the therapeutic effect of the activity of acetylcysteine is in accordance with the current hypothesis that persistent lung injury from fibrosis, and not from inflammation, is the primary pathogenetic mechanism in idiopathic pulmonary fibrosis. [6][7][8][9] On the basis of this hypothesis, there has been particular interest in antifibrotic drugs, 7 such as pirfenidone, 43,44 and in immune modulators, especially interferon gamma-1b. [45][46][47] In a recent double-blind study, pirfenidone was shown to improve vital capacity and to prevent acute exacerbations of idiopathic pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was not our aim to examine whether the therapeutic effect of the activity of acetylcysteine is in accordance with the current hypothesis that persistent lung injury from fibrosis, and not from inflammation, is the primary pathogenetic mechanism in idiopathic pulmonary fibrosis. [6][7][8][9] On the basis of this hypothesis, there has been particular interest in antifibrotic drugs, 7 such as pirfenidone, 43,44 and in immune modulators, especially interferon gamma-1b. [45][46][47] In a recent double-blind study, pirfenidone was shown to improve vital capacity and to prevent acute exacerbations of idiopathic pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs tried or on trial are Etanercept, Imatinib, Prednisone (Daniil et al, 1999;Douglas et al, 1997;Douglas, Ryu, & Schroeder, 2000;Douglas et al, 1998;Nicholson AG, 2000;Riha et al, 2002;Ziesche, Hofbauer, Wittmann, Petkov, & Block, 1999), N-Acetylcysteine (Demedts et al, 2005), TGF-ÎČ antibody (Genzyme, 2007), Interferon-Îł (Antoniou et al, 2006;Raghu et al, 2004;Raghu R, 2001), Interferon-ÎČ (Raghu, Bozic, & Brown, 2001), Pirfenidone (Azuma, Nukiwa et al, 2005;S. Nagai et al, 2002;Raghu, Johnson, Lockhart, & Mageto, 1999), Colchicine (Douglas, Ryu, & Schroeder, 2000;Douglas et al, 1998;Selman et al, 1998), Bosentan, Cyclosporin-A (Alton, Johnson, & Turner-Warwick, 1989;Moolman, Bardin, Rossouw, & Joubert, 1991), D-Penicillamin (Chapela, Zuniga, & Selman, 1986;Selman et al, 1998), Heparin (Kubo et al, 2005), Relaxin (ATS, 2002), Angiotensin converting enzyme (ACE) inhibitors (Nadrous, Ryu, Douglas, Decker, & Olson, 2004), and CTGF antibodies (Mageto Y, 2004). Interestingly, azathioprine and cyclophosphamide, two drugs that are still in the current ATS/ERS guidelines for IPF treatment (ATS, 2002), have never been evaluated in the bleomycin model as far as we know.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…This causes a stiff lung with concomitant abnormalities of gas exchange as the alveolar-capillary membranes widen from increased deposition of extracellular matrix, as the microvascular bed is destroyed by the fibrotic process, and as abnormalities in ventilation-perfusion matching occur (15). As the fibrogenesis progresses, scarring becomes more obvious by radiographic studies, and the disease tends to be even more refractory to successful therapeutic intervention (16).…”
Section: Clinical Concepts Associated With Ipfmentioning
confidence: 99%